Anxiety in Parkinson's disease is associated with changes in the brain fear circuit. (November 2020) - Carey, Guillaume; Lopes, Renaud; Viard, Romain; Betrouni, Nacim; Kuchcinski, Gregory; Devignes, Quentin; Defebvre, Luc; Leentjens, Albert F.G.; Dujardin, Kathy
Abstract: Background: Anxiety is frequent in Parkinson's disease (PD) and has a negative impact on disease symptoms and quality of life. The underlying mechanisms remain largely unknown. The aim of this study was to identify anatomical and functional changes associated to PD-related anxiety by comparing the volume, shape and texture of the amygdala, the cortical thickness as well as the functional connectivity (FC) of the fear circuit in patients with and without clinically relevant anxiety. Methods: Non-demented PD patients were recruited, and anxiety was quantified using the Parkinson Anxiety Scale. Structural MRI was used to compare cortical thickness and amygdala structure and resting-state functional MRI to compare FC patterns of the amygdala and resting-state functional networks in both groups. Results: We included 118 patients: 34 with (A+) and 84 without (A-) clinically relevant anxiety. Clusters of cortical thinning were identified in the bilateral fronto-cingulate and left parietal cortices of the A+ group. The texture and the shape of the left amygdala was different in the A+ group but the overall volume did not differ between groups. FC between the amygdala and the whole brain regions did not differ between groups. The internetwork resting-state FC was higher between the "fear circuit" and salience network in the A+ group. Conclusion: Anxiety in PD induces structural modifications of the left amygdala, atrophy of the bilateral fronto-cingulate and the left parietal cortices, and a higher internetwork resting-state FC between the fear circuit and the salience network. Highlights: Anxiety in Parkinson's disease is associated with a smaller cortical thickness in the "fear circuit". Anxiety in Parkinson's disease is associated with structural changes in amygdala. Anxiety in Parkinson's disease is associated with functional changes between the fear circuit and the salience network. These imaging changes in brain could explain the lower performance in attentional function for these patients.